Association of Vitamin D Levels With Kidney Volume in Autosomal Dominant Polycystic Kidney Disease (ADPKD) - Vendramini, Larissa Collis; Dalboni, Maria Aparecida; de Carvalho Jr., José Tarcísio Giffoni; Batista, Marcelo Costa; Nishiura, José Luiz; Heilberg, Ita Pfeferman (Frontiers in Medicine, 2019)
Vitamin D possesses renoprotective effects beyond mineral metabolism, potentially reducing arterial blood pressure and inflammation and vitamin D enzymes (CYP24A1 and CYP27B1) as well as vitamin D receptor (VDR) contribute to its homeostasis. In the present study, we aimed to determine vitamin D association with kidney volume, blood pressure parameters and inflammatory markers in ADPKD. This cross-sectional study, conducted from August 2011 through May 2016, evaluated 25(OH)D, 1,25(OH)2D and other hormonal/biochemical serum and urinary parameters, inflammatory markers and monocyte expression of VDR, CYP24A1, CYP27B1 in 74 ADPKD patients. The height-adjusted total kidney volume (htTKV) was determined by MRI and blood pressure (BP) measured through 24-hour ambulatory BP monitoring (ABPM).Vitamin D insufficiency was present in 62% of patients and CYP24A1 was overexpressed in this group, raising a hypothesis of 25(OH)D increased catabolism. Serum 25(OH)D levels and VDR expression were negatively correlated with htTKV as was VDR with IL-6, IL-10, CRP and NFκB. A multiple linear regression analysis with htTKV as dependent variable, including hypertension, CRP, eGFR, age, time since diagnosis, VDR and 25(OH)D adjusted for season of the year showed that only the first three parameters were independent predictors of the former.There has been no association of serum 25(OH)D and VDR expression with ABPM parameters. Present findings suggested that low levels of serum 25(OH)D and VDR expression are associated with a higher kidney volume in ADPKD patients, but do not represent independent risk factors for htTKV.